Structure Formation in Soft‐Matter Solutions Induced by Solvent Evaporation. Issue 45 (23rd October 2017) - Zhou, Jiajia; Man, Xingkun; Jiang, Ying; Doi, Masao
Abstract: Solvent evaporation in soft‐matter solutions (solutions of colloidal particles, polymers, and their mixtures) is an important process in material making and in the printing and coating industries. The solvent‐evaporation process determines the structure of materials and strongly affects their performance. Solvent evaporation involves many physicochemical processes: flow, diffusion, crystallization, gelation, glass transition, etc. and is quite complex. Here, recent progress in this important process is reported, with a special focus on theoretical and simulation studies. Abstract : Understanding the solvent‐evaporation process, especially how to control the structural changes during evaporation, is an important subject in many applications. Solutes are kinetically mobile in solution; therefore, the dynamics are fast and the fabrication time can be reduced. The final structure can be controlled by external means such as evaporation rate and solution pH value.